Metachronal waves in magnetic micro-robotic paddles for artificial cilia - Matthew T. Bryan (Nature Portfolio, 2021)
Biological cilia are extremely effective for fluid flow, due to their beating motion creating metachronal waves. Here, metachronal waves are created in micro-robotic paddles that rotate in response to a magnetic field, creating fluid flow speeds of up to 16 μm/s.